2020
DOI: 10.3390/su12135260
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Key Performance Measurement for Manufacturing Operations Management

Abstract: This paper proposes a comprehensive production performance measurement framework and illustrates the method to evaluate the performance and guide practitioners to make further improvement. The development comprises four steps. (1) Performance indicators derived from business excellence models are enumerated to provide the performance model: 74 indicators, which can be classified in terms of their characteristics, are identified in six criteria. (2) A multiple criteria decision-making approach based on the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Side with the SWOT, s urveys may be used to construct a satisfaction index of existing performance measurements (Hwang et al, 2020 ; Shaw, 1999 ).…”
Section: Methods and Discussionmentioning
confidence: 99%
“…Side with the SWOT, s urveys may be used to construct a satisfaction index of existing performance measurements (Hwang et al, 2020 ; Shaw, 1999 ).…”
Section: Methods and Discussionmentioning
confidence: 99%
“…Oysa işletmelerin küresel rekabet ortamında başarılı olabilmeleri için müşteri istek ve ihtiyaçlarını göz önünde bulundurmaları, düşük maliyetle yüksek kaliteli ürünler üretmeleri ve müşterilerine en iyi şekilde hizmet sunabilmeleri gerekmektedir 745 . Bu bakımdan finansal olmayan (operasyonel) performans ve bu performansı ölçme yeteneği, sürekli değişen piyasa şartlarında ayakta kalmak ve sürdürülebilir rekabet avantajı sağlamak açısından önem arz etmektedir 746 .…”
Section: öLçütleriunclassified
“…Bacharz, Raczkiewicz, Bacharz and Grzmil [5] study of precast loggia walls in Poland that had been erected after the Second World War found that they had manufacturing errors that were caused by a concrete cover that did not meet the standard requirements for thickness and tightness. Table 3 shows the typical manufacturing and testing criteria applied to assess product X's performance in this stage, as found by [74] and [34].…”
Section: Manufacturing and Testing Key Performance Indicator (𝑴𝑻 𝒊 )mentioning
confidence: 99%